2007
DOI: 10.1093/ajcn/86.2.341
|View full text |Cite
|
Sign up to set email alerts
|

Intake of phenol-rich virgin olive oil improves the postprandial prothrombotic profile in hypercholesterolemic patients

Abstract: Background: Oxidative stress associated with postprandial lipemia contributes to endothelial dysfunction, which shifts hemostasis to a more thrombogenic state. Objective: We investigated whether a high concentration of phenols in olive oil can partly reverse this phenomenon. Design: Twenty-one hypercholesterolemic volunteers received 2 breakfasts rich in olive oils with different phenolic contents (80 or 400 ppm) according to a randomized, sequential crossover design. Plasma concentrations of lipid fractions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 47 publications
4
50
0
5
Order By: Relevance
“…This original investigation provides novel insight into the relationship between plant foods, specifically strawberry, and cardiovascular health, and supports research showing that a diet high in fruits and vegetables reduces disease risk [27][28][29]47) . We have now shown in both an acute 11,12) and chronic experimental paradigm (present study) that strawberry consumption influences adaptive and compensatory oxidative and inflammatory responses that likely underpin the observed effects on insulin metabolism 5,48) and fibrinolytic/thrombotic activity shown in the present study and by others 44) .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This original investigation provides novel insight into the relationship between plant foods, specifically strawberry, and cardiovascular health, and supports research showing that a diet high in fruits and vegetables reduces disease risk [27][28][29]47) . We have now shown in both an acute 11,12) and chronic experimental paradigm (present study) that strawberry consumption influences adaptive and compensatory oxidative and inflammatory responses that likely underpin the observed effects on insulin metabolism 5,48) and fibrinolytic/thrombotic activity shown in the present study and by others 44) .…”
Section: Discussionsupporting
confidence: 63%
“…We assessed the effects of chronic strawberry feeding on these endpoints in the basal state (fasting measures) and when the body was in a state of physiological stress (postprandial/fed-state measures); with the latter suggested as a better indicator of disease risk [24][25][26] . An improved inflammatory and thrombotic status has been reported after chronic fruit and vegetable consumption as well as after chronic consumption of specific polyphenol-rich foods, including strawberry [27][28][29] . In contrast to these reports, we observed no statistically significant changes in fasting indices of inflammation, platelet function or fibrinolytic activity; although marginal effects (p 0.05-0.1) were evident for inflammatory indices.…”
Section: Discussionmentioning
confidence: 99%
“…4 Moreover, HT is involved in the inhibition of lipid and protein oxidation in human plasma, 5 having anti-inammatory 6 and antiplatelet aggregation properties. 7 Additionally, there is evidence that olive oil phenolic compounds decrease plasma glucose levels in rats. 8,9 HT can be efficiently recovered from olive by-products, which has prompted the study of the biological and health effects of HT from alperujo 8,10 or olive leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In five of the human intervention studies (Estevez-Gonzalez et al, 2010;Haban et al, 2004;Perona et al, 2011;Ruano et al, 2007;Violante et al, 2009), as well as in one animal study (MangasCruz et al, 2001), the content of hydroxytyrosol or its derivatives (e.g. oleuropein complex) in the olive oils administered in the studies was not reported.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 1639)mentioning
confidence: 99%